Influence of carbon and nitrogen sources on GABA production by Levilactobacillus brevis CRL 2013 in chemically defined media - Cataldo, Pablo Gabriel (2021)
Gamma-aminobutyric acid (GABA) is a non-protein amino acid widely distributed in nature, having diverse physiological functions and great potential health benefits. Due to its relevance, GABA is becoming recognized as an essential nutrient for a healthy and balanced diet. Levilactobacillus brevis species, constitute the most competitive and technologically relevant group of microorganisms used to synthesize GABA since they are able to produce high levels of this compound within a variety of food matrices. Glutamic acid decarboxylase (GAD) system is responsible for glutamate decarboxylation and GABA secretion and consists of two important elements: a glutamate/GABA antiporter GadC and a GAD enzyme, either GadA or GadB. In addition, most L. brevis strains encode a transcriptional regulator, gadR, immediately upstream of the gadCA operon which positively regulates its expression. Previously, we demonstrated that CRL 2013 is able to grow and produce high amounts of GABA in fructose-supplemented MRS rich medium with a conversion rate of glutamate to GABA 99%. Furthermore, GABA synthesis was impaired when this strain was grown at the expense of pentoses as the only carbon source. This impairment on GABA production was partially overpassed by the addition of ethanol to the culture media. Interestingly, CRL 2013 was unable to produce GABA after incubation in a chemically defined medium (CDM). Thus, the aim of this study was to analyze the effect of the carbohydrate and nitrogen source on the growth and GABA production by L. brevis CRL 2013 using a CDM. The addition of different nitrogen sources such as casitone (C), vegetal peptone (VP) and yeast extract (YE) stimulated the growth of CRL 2013 in both hexose and pentose- based CDM. Nevertheless, GABA synthesis could only be triggered in the presence of hexoses and YE, C or PV being highest in YE. Conversely, with xylose as the only carbon source, the supplementation of the basal CDM with several nitrogen sources did not allow GABA production and only low GABA levels were detected after 72 h of incubation in the presence of YE. In an attempt to restore GABA production, ethanol (0,25 g/L) was added to the xylose-CDM. Interestingly, the addition of ethanol could restore partially GABA production in the presence of YE. In order to gain insight to the transcriptional changes that could be associated to GABA production, the expression of genes encoding key enzymes and regulatory elements within the GAD system and of the ccpA gene, involved in catabolite repression, was assessed through RT-qPCR using recA as the housekeeping gene. In the hexose- CDM, the expression of gadR and gadA was significantly increased in the presence of C and YE in both exponential and stationary growth phases in comparison with the non-supplemented CDM. At 24 h, gadR was overexpressed 112 and 90 times in the presence of YE and C respectively, when compared to the control CDM. Moreover, the expression levels of gadA were 2800 and 1000 times higher in the presence of YE and C respectively, when compared to the same control. However, when transcription levels were compared against the YE-supplemented xylose CDM (YE-xCDM) at 24 h, gadA and gadR were upregulated 1000 and 200 times respectively, in the presence of hexoses. The addition of ethanol to the YE-xCDM was translated into significantly higher gadA and gadR transcript levels compared with the same medium without ethanol (190 and 275- fold change respectively). Furthermore, no significant differences were observed for gadB while ccpA was 50 times upregulated in the presence of glucose and fructose when compared to the YE-xCDM, which was compatible with an active catabolite repression. Additionally, the expression profiles revealed that gadA and gadR were upregulated and gadB downregulated in the stationary growth phase in the presence of hexoses, whereas the opposite behavior was observed in the presence of xylose. This pattern was reversed after the addition of ethanol to YE-xCDM. To our knowledge, this is the first report regarding the impairment of the GAD system in the presence of pentoses as sole carbon sources and the restoration of GABA production upon ethanol supplementation in a CDM context within lactic acid bacteria. Taken together, these results contribute to the understanding of the regulation of the GAD system in LAB and highlight the potential use of alternative carbon sources to produce high GABA levels.